Assessing the Impact of Media Stream Packet Size Adaptation on Wireless Multimedia Applications - Ukommi, Ubong (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
Multimedia applications constitute greater percentage of traffic in wireless networks. Thus, require investigation of factors influencing effective delivering of media contents in the future, which will include not only conventional multimedia broadcast, but also video streaming to users on demand while meeting the expected quality requirements. In this article, analysis of effect of media packet size adaptation on quality performance of multimedia application is presented. Experiments were performed using standard test media sequences. The encoded media streams at different packet sizes were transmitted over wireless channel at different channel conditions. The quality performance of received media streams were measured using Peak to Signal Noise Ratio (PSNR) software tool to assess the impact of media packet adaptation on quality performance of multimedia applications. A comparative quality performance under same poor channel condition, shows that small media packet size of 256 bytes recorded the highest received quality performance of 22.52dB, compared to the quality performance of 21.87dB for 384 bytes, 21.37dB for 512 bytes, 20.68dB bytes for 640 bytes and 19.47dB for 768 byes, respectively. The findings show media packet size and channel conditions have significant impact on the quality performance of wireless multimedia applications.